2010
DOI: 10.1007/s11845-010-0502-6
|View full text |Cite
|
Sign up to set email alerts
|

How effective is amniotomy as a means of induction of labour?

Abstract: Amniotomy is a simple, safe and effective method of induction of labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In line with previous studies that evaluated waiting 4-24 h after amniotomy, [3][4][5][6][7][8]10 we found that women desiring a 'short delay' after an amniotomy may reduce their likelihood of needing oxytocin without significantly prolonging labour. Parous women and those with a more favourable cervix during amniotomy were more likely to avoid oxytocin, which may assist informed decision-making.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous studies that evaluated waiting 4-24 h after amniotomy, [3][4][5][6][7][8]10 we found that women desiring a 'short delay' after an amniotomy may reduce their likelihood of needing oxytocin without significantly prolonging labour. Parous women and those with a more favourable cervix during amniotomy were more likely to avoid oxytocin, which may assist informed decision-making.…”
Section: Discussionsupporting
confidence: 90%
“…2 Not all women choose to commence oxytocin immediately after amniotomy, and most will labour eventually. In randomised controlled trials, [3][4][5][6] most women who wait after amniotomy are in established labour within 24 h and do not require oxytocin at any stage during labour. Waiting after amniotomy is associated with a significantly longer amniotomy-to-delivery interval.…”
Section: Introductionmentioning
confidence: 99%
“…2 Labor occurs within 24 hours of amniotomy for labor induction in 90.1% of women. 3 However, a Cochrane review concludes that data are lacking about the value of amniotomy alone for induction of labor, but there remain clinical scenarios in which amniotomy alone may be desirable and appropriate and this method is worthy of further research. 4 Another Cochrane review states that amniotomy and oxytocin infusion can induce labor, but the optimal timing of oxytocin infusion after amniotomy is not known.…”
mentioning
confidence: 99%
“…Artificial rupture of membranes (AROM) is a non-pharmacological mode of IOL, with high success rates especially in multiparous women [ 17 ]. To date, little is known about the efficacy of AROM as a mode of IOL in women with a previous cesarean section.…”
Section: Backroundmentioning
confidence: 99%